Evaluation of a community pharmacy dispensing process using a Coloured Petri Net - Naybour, M.; Remenyte-Prescott, R.; Boyd, M. (2018)
UK customers visited community pharmacies to receive NHS prescriptions 1.104 billion times in 2016. One study of dispensing errors found an error rate of 3.3%. Severe dispensing inaccuracies often receive a high level of media attention, however, lower level errors could also be causing significant inefficiencies in the delivery of primary healthcare. This paper presents a modelling approach for analysing the reliability and efficiency of community pharmacies performance using a Coloured Petri Net (CPN) methodology. The model consider show single prescriptions are processed, the use of staff resources, and the occurrence of errors. The CPN evaluates performance over a set of key performance indicators. Results are validated, where possible, against published studies of community pharmacies.